O melhor da arte do renascimento - Alfredo J. Morale, Salvador Andrés Ordax, Ernesto Arce Oliveira (G & Z, 1997)
17.º vol.: Alfredo J. Morales 47 p.; 18.º vol.: Salvador Andrés Ordax, 47 p.; 19.º vol.: Ernesto Arce Oliveira, 47 p.